La3+-doped CeO2 system: Negating the myths with a tailor-made ceramic. (December 2018) - Kumar, Kundan; Srivastava, Saurabh; Chowdhury, Anirban
Abstract: In spite of promising functional properties, La2 Ce2 O7 finds limited mention in the research community due to various materials issues (e.g., phase stability and retention, sinterability, modest thermal conductivity etc.). We show when these issues are suitably taken cared off, the same system depicts a total conductivity of 10.8 × 10 −2 S/cm, the highest till date for any La 3+ -doped CeO2 matrix. Our achievement of such property was assisted by a near-theoretical density ( 98%), highly textured (Lotgering factor 0.9) ceramic via conventional sintering; the texturing did not involve any extra/additional processing operations (e.g., templated grain growth, tape casting, hot forging etc.). Graphical abstract: Unlabelled Image